Do Public Service Values Transform Primary Healthcare Quality? - Regan Vaughan; Ferdyansyah Wicaksono; Soma Gantika (Jurnal Borneo Administrator, 2026)
This study examines the quality of national health insurance services at the South Sumedang Health Centre through the lens of public service values. In Indonesia, primary healthcare centres are mandated to deliver equitable and accountable services, yet they often operate under limited resources and infrastructure. This research aims to evaluate how public service principles, namely equity, transparency, and accountability, are reflected in the implementation of healthcare services at thelocal level. A qualitative descriptive approach was used, involving interviews, observations, and document analysis. The evaluation framework adopts five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. Findings reveal that while the assurance and empathy dimensions are relatively strong, particularly in staff behaviour and attentiveness, the health centre faces considerable challenges in infrastructure, staff availability, and administrative responsiveness. Tangible aspects, such as overcrowded waiting rooms and the lack of digital registration systems, hinder service efficiency. In terms of reliability and responsiveness, service delays and insufficient personnel affect patient satisfaction. The study concludes that although the South Sumedang Health Centre demonstrates commendable efforts to ensure compassionate care, systemic improvements are necessary. Recommendations include infrastructure upgrades, digital systemintegration, and enhanced staff capacity through targeted training. This research offers practical insights for health administrators and policymakers to improve service delivery in resource-constrained settings. It reinforces the importance of aligning healthcare services with core public service values.